APLIKASI MODEL PROBABILISTIK UNTUK SIMULASI ALIRAN MATERIAL ERUPSI STUDI KASUS: GUNUNG MERAPI, JAWA TENGAH - Yulianto, Fajar; Parwati, Parwati (Institut Teknologi Sepuluh Nopember, 2012)
Simulation of eruption material flow using probabilistic model based on the Monte Carlo algorithm was conducted in this research. The simulation result was used to support the creation of zoning map of volcanic hazards and the estimation of building number which has possibility to be impacted by the Merapi Volcano eruption. Input data for the simulation was Digital Elevation Model - Shuttle Radar Topographic Mission (DEM-SRTM) with a spatial resolution of 30 meters. In addition, GeoEye satelit imagery in 2009 was used to renew settlement information of the RBI map from BAKOSURTANAL. The simulation result of material flow eruption was overlaid with building area information to estimate the magnitude of eruption impact. The simulation results from this research has similar pattern and similar eruption material distribution with the reference map (volcanic hazard map of Merapi). The flow of Merapi eruption material generally leads to the south through the Gendol Rivers to Cangkringan, and to the southwest ward through the Puth Rivers to Srumbung. Material flow eruption is shown in height simulations 2 meters and 7 meters. The wider and widening of the simulation models material flow eruption generated, the greater impact on the settlements in the vicinity of Merapi Volcano.